2004
DOI: 10.1016/j.bbmt.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic graft-versus-host disease after ablative and nonmyeloablative conditioning for allogeneic hematopoietic transplantation

Abstract: In this study, we evaluated the influence of nonmyeloablative and ablative conditioning regimens on the occurrence of acute and chronic graft-versus-host disease (GVHD). One hundred thirty-seven patients undergoing matched-related sibling transplantations received the same GVHD prophylaxis. Myeloablative regimens included intravenous busulfan/cyclophosphamide (n=45) and fludarabine/melphalan (n=29). Patients in the nonmyeloablative group (n=63) received fludarabine/idarubicin/cytarabine, cisplatin/fludarabine/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(126 citation statements)
references
References 18 publications
8
115
2
1
Order By: Relevance
“…The first interaction between activated host APCs and donor T cells likely takes place in the lymphoid tissues associated with gastrointestinal tract (Peyer's patches) [23]. For the same reason reduced intensity conditioning causes less aGVHD as there is decreased damage from the conditioning regimen to the host tissue leading to less activation of the immune cascade [24,25]. In nonclinical models GVHD can be reduced via manipulation of APCs as well [26,27].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The first interaction between activated host APCs and donor T cells likely takes place in the lymphoid tissues associated with gastrointestinal tract (Peyer's patches) [23]. For the same reason reduced intensity conditioning causes less aGVHD as there is decreased damage from the conditioning regimen to the host tissue leading to less activation of the immune cascade [24,25]. In nonclinical models GVHD can be reduced via manipulation of APCs as well [26,27].…”
Section: Pathophysiologymentioning
confidence: 99%
“…37,39 In our original reports, the incidence of grade II to grade IV aGVHD ranged between 40 and 60% following myeloablative unrelated HLA 2-3 antigen disparate UCBT in pediatric recipients. 2,3 Couriel et al 60 and Mielcarek et al 61 have suggested a reduced incidence of aGVHD in adult recipients following RI-AlloSCT. Our results are consistent with these findings of potentially reduced aGVHD following RI conditioning and UCBT in pediatric recipients.…”
Section: Survivalmentioning
confidence: 99%
“…This patient might also have had age-related renal dysfunction, his renal function being more susceptible to insults including GVHD. Alternatively, differences in the pathogenesis of acute GVHD between conventional myeloablative allo-SCT and RIST 11,12 might have contributed to the development of renal tubulitis in this patient.…”
mentioning
confidence: 98%